Analysis Evacuation Route for KM Zahro Express on Fire Condition using Agent Based Modeling and Fire Dynamics Simulatior - Trika Pitana; Muhammad Badrus Zaman; Dioco Carlos Kristian Perdana; Aleik Nurwahyudi (Institut Teknologi Sepuluh Nopember, 2017)
Safety is the thing that needs to be preferred by users of transport, passengers should also understand about safety procedures and evacuation procedures in the means of transport. There have been many accidents that happen in the world of transport, particularly in the shipping world, from 2010 to 2016 is no more than 50 accidents of ships in accordance with the cause recorded by KNKT (Komisi Nasional Keselamatan Transportasi). On this research was discussed the evacuation time on the ship KM Zahro express that occurred earlier in the year 2017 in the Kepulauan Seribu, DKI Jakarta. Almost all passenger dead caused by fire from power source in engine room. This thesis will explaine about evacuation time and dangers from fire that interfere the process of evacuation. The methods used are Agent Based Modeling and Simulation (ABMS) and Fire Dynamics Simulator (FDS) for modeling fire simulation. Agent-Based Modeling software (pathfinder) and Fire Dynamics Simulator software (pyrosim) are used to calculate time evacuation in normal condition and fire condition of KM Zahro Express. Agent-Based Modeling and Simulator (ABMS) is a modeling method that aims to model complex problems based on real cases. Agent-Based Modeling and Simulator (ABMS) is designed to model a place that has a seat, path, exit door, humans, and others. Pyrosim is a graphical user interface for the Fire Dynamics Simulator (FDS). FDS models can predict smoke, temperature, carbon monoxide, and other substances during fires. In this case the existing models can be used to plan and prepare an emergency if unwanted things happen. As well as using basic rules which refer to the Safety Of Life At Sea (SOLAS) and International Maritime Organization (IMO). Result of Evacuation simulation calculation on emergency conditions (two rear exit doors will be closed) that match at actually condition is 29,783 minutes (respon is not taken in this simulation), calculation results obtained from simulation of evacuation (Traveling Time) and at the count expanded feet according to the IMO formula (performance standard). From fire simulation could be analyzed the time and the amount of smoke on deck. It can be seen that in the 1800 seconds smoke levels produced in the relatively high place so disturbing in the evacuation process.